Enterprise Package Management: A Framework for Secure Development and Team Collaboration - Kartheek Medhavi Penagamuri Shriram, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article presents a comprehensive analysis of software supply chain security in modern development environments, focusing on package management and security practices. It examines the critical challenges organizations face in managing open-source dependencies, where the majority of application code comes from external sources. The article explores essential security measures including package source mapping, multi-factor authentication requirements, vulnerability notifications, and central package management systems. Through detailed analysis of recent security trends, including the significant increase in security advisories and package downloads, the article demonstrates the growing importance of supply chain security. It presents practical solutions for vulnerability management, dependency tracking, and secure package source configuration while incorporating emerging technologies such as OIDC, build provenance, and automated vulnerability remediation. The article emphasizes the critical role of proactive security measures and best practices in maintaining secure software development environments, particularly in enterprise settings where package management security directly impacts organizational risk and operational efficiency.
Keywords: Software Supply Chain Security; Dependency Management; Enterprise Security; Vulnerability Detection; Package Repository Protection